The Utilization of Flipgrid in Learning English Speaking Skill for EFL Teachers in Muhammadiyah Schools - Tri Wintolo Apoko; Isa Faqihuddin Hanif; Soya Amelia Putri (Jurnal Pengabdian UNDIKMA, 2022)
This community service aimed to introduce the utilization of Flipgrid in learning English speaking skill for EFL teachers. There were 31 EFL teachers that consisted of 22 female teachers and 9 male teachers who participated in this activity. The method used in this activity was a training which discussed the concept of Flipgrid application and demonstrated it for the practice of speaking skill. The instruments used were questionnaire and semi-structure interview. The collected data were analyzed with descriptive analysis to provide mean and standard deviation for the questionnaire data and with qualitative analysis for interview data. The result of this activity showed that the materials of the training were suitable with EFL teachers’ need in enhancing English speaking learning activity at schools. In addition, all the EFL students had positive perceptions on the use of Flipgrid in increasing the quality of speaking skill as Flipgrid was easy to operate and access as well as it was useful for any modes of learning situations. It is thus recommended that Flipgrid be good to use by EFL teachers for the students’ English-speaking practice.